Accumulation of heavy metals in soil and maize after 17-year pig manure application in Northeast China - Zhou, Changrui; Ma, Qiang; Yu, Wantai; Xia, Zhuqing; Ning, Chuanchuan; Yuan, Haiyan; Li, Shuailin (Plant, soil and environment, 2020)
Application of composted pig manure (PM) is a traditional practice to improve soil fertility, whereas generally leads to some environmental questions. The effects of PM application on Cd, Cu and Zn accumulation in soil and maize were investigated based on a long-term field trial in Northeast China, including control (CK), PML, PMM, and PMH, receiving 0, 100, 250 and 500 kg total N/ha/year from 2002 to 2008 and 0, 10, 25 and 50 t fresh weight/ha/year from 2009 to 2018, respectively. Results showed that long-term soil application of PM increased maize grain yield, soil organic carbon (SOC) contents, coupled with significant accumulation and availability of Cd, Cu, and Zn in soil (0–15 cm). Compared with CK, the soil total Cd, Cu and Zn concentrations significantly increased by 105, 287 and 108% at high PM rate, respectively. Notably, the increments enhanced these heavy metals storage in maize roots rather than in grains. Moreover, the application of PM confirmed vertical transport of heavy metals in the tested soil, particularly for Cd and Cu in PMH treatment. Overall, the repeated application of PM can cause the accumulation and leaching of Cd, Cu and Zn in soil.